The collector - Roberts, Nora (New York Little, Brown and Company, 2014)
When professional house-sitter Lila Emerson witnesses a murder/suicide from her current apartment-sitting job, life as she knows it takes a dramatic turn. Suddenly, the woman with no permanent ties finds herself almost wishing for one. Artist Ashton Archer knows his brother isn't capable of violence--against himself or others. He recruits Lila, the only eyewitness, to help him uncover what happened. Ash longs to paint her as intensely as he hungers to touch her. But their investigation draws them into a rarefied circle where priceless antiques are bought, sold, gambled away, and stolen, where what you possess is who you are, and where what you desire becomes a deadly obsession
Keywords: Antiques -- Fiction; Theft -- Fiction; Witnesses -- Fiction; Murder -- Investigation -- Fiction; Artists -- Fiction; Electronic books; Romantic suspense fiction